IMPLEMENTATION OF NETWORK SECURITY USING WORMHOLE ATTACK - Dr. B. Padminidevi, Mrs.C.Selvarathi (International Journal of Advanced Science and Technology, 2020)
Computer Network is playing a major role to transfer the data or message from one place to another place.In a fashionable world no one can live without interner.It is a basic  feature to  transferring or exchanging a message. In a growth of network having verities of network like Mobile Adhoc Network(MANET),Wirless Network,Wired Network,Wireless Sensor Network, etc. Among all varieties of network this will concentrate on Wireless Sensor network(WSN).Moreover all network path having the attackers to hack the path or data from the owner of the data. WSN is the autonomous nature in working.here find the attackers and prevent the attackers process to safeguard the data Since the transformation of data should have the property of integrity.To Send the data from source to destination with the short time.using AOMDV protocol .here Warmhole attack is identified and prevent the attack from the attacker.